Endocan: A Biomarker for Hepatosteatosis in Patients with Metabolic Syndrome - Hande Erman; Engin Beydogan; Seher Irem Cetin; Banu Boyuk (Mediators of Inflammation, 2020)
Background. Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases, which has recently been mentioned as an independent cardiovascular risk factor. Objectives. Endocan is a novel molecule of endothelial dysfunction. We aimed to evaluate the associations of serum endocan levels with the hepatic steatosis index (HSI), fatty liver index (FLI), and degrees of hepatosteatosis in patients with metabolic syndrome with NAFLD. Design and Setting. This cross-sectional prospective study was performed in the outpatient clinic of an internal medicine department. Methods. The study included 40 patients with metabolic syndrome with NAFLD as noted using hepatic ultrasound and 20 healthy controls. Secondary causes of fatty liver were excluded. FLI and HSI calculations were recorded. Serum endocan level values were obtained after overnight fasting. Results. Higher values of HSI and FLI were found in the NAFLD groups than in the control groups (p<0.001). Five (12.5%) of 20 patients with liver steatosis had grade 1 liver steatosis, 15 (37.5%) patients had grade 2 liver steatosis, and 20 (50%) patients had grade 3 liver steatosis. Serum endocan levels were lower in patients with NAFLD compared with the healthy controls (146.56±133.29 pg/mL vs. 433.71±298.01 pg/mL, p<0.001). ROC curve analysis suggested that the optimum endocan value cutoff point for NAFLD was 122.583 pg/mL (sensitivity: 71.79%, specificity: 90%, PPV: 93.3%, and NPV: 62.1%). Conclusion. Serum endocan concentrations are low in patients with NAFLD, and the optimum cutoff point is 122.583 pg/mL. HSI and FLI were higher in patients with NAFLD; however, there was no correlation with serum endocan.